Four Variants of the Citrobacter freundii AmpC-Type Cephalosporinases, Including Novel Enzymes CMY-14 and CMY-15, in a Proteus mirabilis Clone Widespread in Poland - Literacka, Elżbieta (American Society for Microbiology, 2004)
Twenty-nine Proteus mirabilis isolates from 17 Polish hospitals were analyzed. The isolates were resistant to a variety of antimicrobials, and their patterns of resistance to β-lactams resembled those of the constitutive class C cephalosporinase (AmpC) producers. Indeed, β-lactamases with a pI of ∼9.0 were found in all of the isolates, and they were subsequently identified as four AmpC-type cephalosporinases, CMY-4, -12, -14, and -15, of which the two last ones were novel enzyme variants. The enzymes were of Citrobacter freundii origin and were closely related to each other, with CMY-4 likely being the evolutionary precursor of the remaining ones. The bla(CMY) genes were located exclusively in chromosomal DNA, within EcoRI restriction fragments of the same size of ∼10 kb. In the CMY-12- and -15-producing isolates, an additional fragment of ∼4.5 kb hybridized with the bla(CMY) probe as well, which could have arisen from a duplication event during the evolution of the genes. In all of the isolates, the ISEcp1 mobile element, which most probably is involved in mobilization of the C. freundii ampC gene, was placed at the same distance from the 5′ ends of the bla(CMY) genes, and sequences located between them were identical in isolates carrying each of the four genes. These data suggested that a single chromosome-to-chromosome transfer of the ampC gene from C. freundii to P. mirabilis could have initiated the spread and evolution of the AmpC-producing P. mirabilis in Poland. The hypothesis seems to be confirmed by pulsed-field gel electrophoresis typing, which revealed several cases of close relatedness between the P. mirabilis isolates from distant centers and showed an overall similarity between the majority of the multiresistant isolates.